(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the integration of multimedia technologies into Russian language instruction within non-philological universities. Given the diverse academic backgrounds of students in such institutions, traditional language teaching methods often fall short in engaging learners. Multimedia tools—encompassing video, audio, interactive platforms, and gamified content—offer dynamic alternatives that cater to various learning styles and enhance linguistic proficiency. This study examines the theoretical foundations, practical applications, and pedagogical benefits of multimedia in language education, aiming to provide a comprehensive overview for educators and curriculum developers.